Trypanosomatid Richness Among Rats, Opossums, and Dogs in the Caatinga Biome, Northeast Brazil, a Former Endemic Area of Chagas Disease - Dario, Maria Augusta; Furtado, Carolina; Lisboa, Cristiane Varella; de Oliveira, Felipe; Santos, Filipe Martins; D’Andrea, Paulo Sérgio; Roque, André Luiz Rodrigues; Xavier, Samanta Cristina das Chagas; Jansen, Ana Maria (Frontiers in Cellular and Infection Microbiology, 2022)
Parasites are important components of the immense n-dimensional trophic network that connects all living beings because they, among others, forge biodiversity and deeply influence ecological evolution and host behavior. In this sense, the influence of Trypanosomatidae remains unknown. The aim of this study was to determine trypanosomatid infection and richness in rats, opossums and dogs in the semiarid Caatinga biome. We submitted DNA samples from trypanosomatids obtained through axenic cultures of the blood of these mammals to mini exon multiplex-PCR, Sanger and next generation sequencing targeting the 18S rDNA gene. Phylogenetic analyses were performed to identify genetic diversity in the Trypanosomatidae family. Shannon, Simpson, equability, and beta-diversity indices were calculated per location and per mammalian host. Dogs were surveyed for trypanosomatid infection through hemocultures and serological assays. The examined mammal species of this area of the Caatinga biome exhibited an enormous trypanosomatid species/genotypes richness. Ten denoised Operational Taxonomic Units (ZOTUs), including four species (Trypanosoma cruzi, Trypanosoma rangeli, Crithidia mellificae and Trypanosoma sp.), five genotypes/lineages (T. cruzi DTU TcI, TcII and TcIV; T. rangeli A and B) and four DTU TcI haplotypes (ZOTU1, ZOTU2, ZOTU5 and ZOTU10 merged), as well as 13 Amplicon Sequence Variant (ASV), including five species (T. cruzi, T. rangeli, C. mellificae, Trypanosoma dionisii and Trypanosoma lainsoni), five genotypes/lineages (same as the ZOTUs) and seven DTU TcI haplotypes (ASV, ASV1, ASV2, ASV3, ASV5, ASV10m, and ASV13), were identified in single and mixed infections. We observed that trypanosomatids present a broad host spectrum given that species related to a single host are found in other mammals from different taxa. Concomitant infections between trypanosomatids and new host-parasite relationships have been reported, and this immense diversity in mammals raised questions, such as how this can influence the course of the infection in these animals and its transmissibility. Dogs demonstrated a high infection rate by T. cruzi as observed by positive serological results (92% in 2005 and 76% in 2007). The absence of positive parasitological tests confirmed their poor infectivity potential but their importance as sentinel hosts of T. cruzi transmission.